VIRTUAL IDENTITY ON SOCIAL MEDIA: AN ANALYSIS OF THE SECOND ACCOUNT AND FAKE ACCOUNT PHENOMENON IN SOCIAL REPRESENTATION - Agung Wibisono; Tri Febri Kurniawan (MediaKom : Jurnal Ilmiah Komunikasi, 2026)
This research is motivated by the increasing use of social media, which encourages the formation of virtual identity through the practice of secondary accounts and fake accounts. The aim of this study is to analyze the construction of virtual identity among Generation Z within the framework of Moscovici’s Social Representation Theory (SRT), emphasizing the processes of anchoring and objectification in the formation of social meaning. The initial hypothesis suggests that digital identity is fragmented and contextual, depending on the social function of each account. This study employs a descriptive qualitative approach within the constructivist paradigm. The research subjects consisted of eight Generation Z informants who are active on social media and have alternative accounts. Data were collected through in-depth interviews, digital observation, and documentation, then analyzed using open coding, axial coding, and selective coding, along with thematic analysis based on SRT. The findings reveal that virtual identity is formed in three main layers: the main account as a curated public representation, the secondary account as a space for personal and emotional expression, and the fake account as a tool for anonymity and social observation. These results align with previous studies that position alternative accounts as impression management strategies, yet extend them within the context of social representation and power relations. The processes of anchoring and objectification are evident through digital symbols such as usernames, language styles, and interaction patterns. This study concludes that virtual identity is an adaptive and layered social construct, serving as a communication strategy for negotiating public–private boundaries, social control, and authenticity in the digital space.